2013
DOI: 10.1371/journal.pone.0056059
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Survival in a Neotropical Migratory Songbird Is Lower than Expected

Abstract: Attempts to estimate and identify factors influencing first-year survival in passerines, survival between fledging and the first reproductive attempt (i.e. juvenile survival), have largely been confounded by natal dispersal, particularly in long-distance migratory passerines. We studied Prothonotary Warblers (Protonotaria citrea) breeding in nest boxes to estimate first-year survival while accounting for biases related to dispersal that are common in mark-recapture studies. The natal dispersal distribution (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 46 publications
4
57
0
Order By: Relevance
“…For instance, because adult birds are typically considered highly philopatric (e.g., Greenwood andHarvey 1982, Holmes and, natal dispersal distances will often determine distances between interacting sites of population sources and population sinks. A few previous studies have found correlations in the abundance of passerine birds from one year to the next in areas 2-100 km apart, which is evidence of source-sink dynamics at this spatial scale (Winkler et al 2005, Tittler et al 2006, McKim-Louder et al 2013). However, the geographic scales at which source-sink dynamics operate in avian ecology remain poorly understood.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, because adult birds are typically considered highly philopatric (e.g., Greenwood andHarvey 1982, Holmes and, natal dispersal distances will often determine distances between interacting sites of population sources and population sinks. A few previous studies have found correlations in the abundance of passerine birds from one year to the next in areas 2-100 km apart, which is evidence of source-sink dynamics at this spatial scale (Winkler et al 2005, Tittler et al 2006, McKim-Louder et al 2013). However, the geographic scales at which source-sink dynamics operate in avian ecology remain poorly understood.…”
Section: Discussionmentioning
confidence: 77%
“…High site fidelity for adult shrubland birds has been shown to occur even in landscapes where suitable habitat is less clustered than it is in our site (Holmes and Sherry, 1992;Lehnen and Rodewald, 2009). One reason for our relatively high natal return rates could be because of the large number of locally suitable territories for prairie warblers in our compact study area in relation to the surrounding landscape, allowing us to detect birds that survived and returned at a local scale (Fajardo et al, 2009;McKim-Louder et al, 2013). Nevertheless, the study site was not completely isolated; multiple power line corridors and other early-successional habitats within 5 km of the study site provided suitable prairie warbler habitat that held territorial singing males.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that our estimated HY Φ is no different than previous HY Φ estimates when taking into account the approximate 95% confidence interval, i.e., the SE of ±0.06. All three of these HY Φ estimates are well above the HY Φ mean ± SE estimates reported for Prothonotary Warblers, which are 0.06 ± 0.01 and 0.11 ± 0.01, with and without cowbird nestmates, respectively (McKim-Louder et al 2013). However, Φ estimates are not directly comparable between studies.…”
Section: Discussionmentioning
confidence: 47%
“…However, Φ estimates are not directly comparable between studies. McKim-Louder et al (2013) banded young in nest boxes before fledging occurred and had both males and females in their analysis, and Φ for HY birds can be related to an assortment of factors including differences in dispersal patterns among species and/or subpopulations. We currently do not have the data to assess whether the relatively high HY GCWA Φ estimates are an artifact of the individual study plot, are an outcome of the sampling protocol used to band individuals, or are reasonable for this particular species.…”
Section: Discussionmentioning
confidence: 99%